EFEKTIVITAS SENAM HAMIL MENURUT MANUABA TERHADAP NYERI PUNGGUNG IBU HAMIL TRIMESTER III - Ranny Septiani; Islamiyati Islamiyati (Jurnal Ilmiah Kesehatan Media Husada, 2021)
Back pain is one of the most common complaints experienced by pregnant women in their third trimester of pregnancy. Of the 172 pregnant women in the third trimester of pregnancy, 80% (137 people) experienced back pain. One way to deal with back pain is to do pregnancy exercises. There are various types of pregnancy exercises, this study uses pregnancy exercises according to Manuaba. The purpose of this study is to study the effect of pregnancy training according to Manuaba on back pain in pregnant women of the third trimester in Metro City. The design of this study is a pseudo-experimental research with a single group approach. The population in this study was all third trimester pregnant women at the Puskesmas in Metro City. The sampling technique was a temporary sample with a sample of pregnant women in the third trimester with back pain complaints. Data analysis in this study uses univariate analysis with frequency and bivariate percentage analysis with t-test. The results of this study show that there is a difference in back pain before and after pregnancy training, according to Manuaba, with a mean difference of 3.06. In conclusion, there are effects of exercise, according to Manuaba, on back pain in pregnant women. These results are expected to be a source of reference for health workers to perform pregnancy exercises according to Manuaba to pregnant women to reduce back pain in pregnant women.